Built environment life cycle process and climate change - Kaklauskas, A. (2013)
In order to design and realise an efficient built environment life cycle with focus on climate change mitigation and adaptation, it is necessary to carry out exhaustive investigations of all the decision and processes that form it. The efficiency level of the considered built environment life cycle depends on a great many micro, meso and macro factors. The authors of this paper participated in the different EU projects related with built environment and climate change [Linking European, Africa and Asian Academic Networks on Climate Change (LEAN CC), etc.]. One of the LEAN CC project’s goals was to develop a Model and Intelligent System of Built Environment Life Cycle Process for Climate Change Mitigation and Adaptation. The presented Model and Intelligent System enables one to form up to 100 million alternative versions. Intelligent system allows one to determine the strongest and weakest points of each project and its constituent parts. In order to demonstrate the micro, meso and macro factors that influence the efficiency of the built environment in climate change mitigation and adaptation processes, the Model and Intelligent System will be considered as an example.